Karya Pendamaian Kristus: Analisis Efesus 2:11-18 - Thomas Bedjo Oetomo (Jurnal Missio Cristo, 2019)
Abstract: The presence of sin effects extraordinarily to the human’s personality and the relationship to God. The sin radically changes the history, mission, and the purpose of human. The reality of sin brings the effect and the bad consequence to the human, so that the human willingly takes sides to sin and disobey to God’s commandment. Finally, the sin governs over the human. This is such a huge and deathly tragedy. The effect of sin is so deep and fatal. That happens because it’s against to the person and character of God. All things that have no harmony to the person and character of God is sin (2 Corinthians 4:4; Ephesians 4:18; Romans 1:18; 3:20). In the stupidity and pseudo piety, human has a lot of ways to try to bribe God, so that the harmonius fellowship can be rebuilt. There are some people torture themselves and spread out their richness. The Bible says that the human’s effort to restore the broken relationship is useless. The fact is, the restoration is started from God Himself. Therefore, 2000 years ago, God incarnated Himself in Christ Jesus, dead on the cross, rose from the death, and ascended up to heaven as the only restorative way between God and human. Paul in Ephesians 2:11-12 explains clearly about the restoration of Christ.